Hubungan Pengetahuan Gizi Dan Asupan Pangan Dengan Status Gizi Hemodialisa Di Rumah Sakit Umum Hermina Bekasi: Association of nutrition knowledge and dietary intake with nutrition status on hemodialysis outpatient in Hermina Hospital Bekasi - Kurniati, Lilik; Fayasari, Adhila (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2024)
The prevalence of patients on hemodialysis at Hermina Bekasi Hospital increases from year to year. The risk of malnutrition in chronic kidney failure patients on hemodialysis is very high. Several causal factors include nutritional knowledge and intake. This study aims to analyze the relationship between nutritional knowledge, energy and protein intake with the nutritional status of outpatient chronic kidney failure patients on hemodialysis at Hermina Bekasi Hospital. The design of this study was cross sectional, which was carried out at Hermina Bekasi Hospital on 90 subjects in May-June 2018. The research subjects were patients with chronic renal failure on hemodialysis who had undergone hemodialysis for at least one-month, routine HD twice per week, without NGT, can communicate well. Nutritional status was measured using the SGA form, nutritional knowledge using a structured questionnaire and intake was measured using a 3x24 hour food record. Statistical analysis with Chi-square with α 5%. 43% of subjects had poor or poor nutritional status, most of them had good knowledge (55.6%), and had a good intake (energy 52.2% and protein 78.9%). There is a significant relationship between nutritional knowledge and nutritional status (p 0.038; OR 2.447), and a relationship between energy intake and nutritional status (p = 0.000; OR 15.951), as well as protein intake and nutritional status (p = 0.005; OR 5.032). In chronic kidney patients on hemodialysis, knowledge and macronutrient intake are closely related to nutritional status.